ONE-ON-ONE LEARNING METHOD IN SOLVING ENGLISH SPEAKING PROBLEMS: A STUDY ON EFL LEARNERS - Juspaningsih Juspaningsih (International Journal of Research on English Teaching and Applied Linguistics, 2023)
The goal of the current study was to provide more information on one-on-one instruction as a learning approach for EFL learners' English speaking difficulties. The study's main interests were the EFL students' perceptions of one-on-one instruction and the speaking skills they acquired from it. This study employed a qualitative research design. Semi-structured interviews, documentation and speaking activity observation were used as data gathering methods. The researcher included EFL students who take speaking-focused courses at an English course in Makassar in the data collection process. There were ten EFL students available for an interview. After gathering the data, the researcher examined the data using three steps of data analysis; data reduction, data display and conclusion drawing/verification. The findings of this study showed that EFL students had difference opinions about one-on-one instruction. One-on-one instruction, according to them, is good, great, effective, efficient, fun, adaptable, and peaceful. Then, there were certain speaking exercises that EFL learners typically pick up along the learning process to hone their speaking skills. These speaking exercises included role plays, retelling movies, describing images, speaking games like dominos and speaking boards, question and answer sessions, telling daily activities, sharing experiences, outlining preferences, and talking about planning.